Isolation and evolution of novel nucleoside phosphorylases - Visser, Daniel Finsch (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2010)
Approximately 33.4 million people are living with HIV/AIDS. Of those, 97% live in low and middle income countries, with 22.4 million in sub-Saharan Africa. Only 42% of the people who require anti-retrovirals (ARVs) in low to middle income countries are receiving anti-retroviral therapy (ART). There is a need to develop novel and cost effective methods for producing antiretroviral drugs. Stavudine and azidothymidine (AZT) were identified as potential targets because they could both be produced through a common intermediate "“ 5 methyluridine (5-MU). It has been established that the biocatalytic production of 5-methyluridine is possible through a reaction known as transglycosylation, in a process which has not previously been demonstrated as commercially viable. A selection of biocatalysts were expressed either in recombinant E. coli strains or in the wild type organisms, purified and then screened for their ability to produce 5-MU. A combination of Bacillus halodurans purine nucleoside phosphorylase 1 (BHPNP1) and E. coli uridine phosphorylase (EcUP) gave the highest 5-MU yield (80%). This result represents the first combination of free enzymes from different organisms, giving high yields of 5-MU under high substrate conditions. Both enzymes were purified and successfully characterised. The established pH optimum was pH 7.0 for both enzymes. Temperature optima and stability data for BHPNP1 (70 C and t1/2 at 60 C of 20.8 h) indicated that the biocatalytic step was operating within the capabilities of this enzyme and would operate well at elevated temperatures (up to 60 C). Conversely, the temperature optimum and stability data for EcUP (optimum of 40 C and t1/2 at 60 C of 9.9 h) indicated that the enzyme remained active at 40 C for the duration of a 25 h biotransformation, but at 60 C would only be operating at 20% of its optimum activity and would lose activity rapidly. BHPNP1 and EcUP were used in a bench scale (650 ml) transglycosylation for the production of 5-MU. A 5-MU yield of 79.1% was obtained at this scale with a reactor productivity of 1.37 g.l-1.h-1. Iterative saturation mutagenesis was used to rapidly evolve EcUP for improved thermostability. A moderately high throughput colorimetric method was developed for screening the mutants based on the release of p-nitrophenol upon phosphorolysis of a pyrimidine nucleoside analogue. By screening under 20 000 clones the mutant UPL8 was isolated. The mutant enzyme showed an optimum temperature of 60 C and improved stability at 60 C (t1/2 = 17.3 h). The increase in stability of UPL8 is due to only 2 mutations (Lys235Arg, Gln236Ala). These mutations may have caused an increase in stability due to interactions with other structural units in the protein, stabilization of the entrance to the binding pocket, or by decreasing the flexibility of the Î±-helix at the N-terminus. Transglycosylation experiments showed that the mutant enzyme UPL8 is a superior catalyst for the production of 5-MU. A 300% increase in reactor productivity was noted when free enzyme preparations of UPL8 was combined with BHPNP1 at 1.5% m.m-1 substrate loading. The high yield of 5-MU (75-80% mol.mol-1) was maintained at 9% m.m-1 substrate loading. A commercially viable productivity of 31 g.l-1.h-1 was thus realised. Further optimisation of the process could produce still higher productivities. Future work in directed evolution of nucleoside phosphorylases is envisaged for improved stability and enhanced substrate range for application to other commercially relevant transglycosylation reactions.
Keywords: AIDS (Disease) -- Treatment -- Africa; HIV Infections -- Treatment -- Africa; AIDS (Disease) -- Patients -- Africa; HIV-Positive persons -- Africa; Antiretroviral agents; Pyrimidine nucleotides